Economic evaluation of snake antivenom production in the public system - Morais,V. (2006)
Snake antivenom, an expensive animal product, is presently the only effective treatment for the consequences of snakebite. In Latin America, antivenoms are mainly produced by public institutions with frequent shortages of the necessary supply. Here, we present an economical analysis of the factors affecting production cost, assuming a basic processing batch of 100 L hyperimmune plasma. Three annual production volumes were considered for two typical production technologies. The components of cost were classified as fixed, variable and semi-variable. We found that in all stages of production, fixed cost represents the major contribution to total cost, and is given essentially by manpower cost, particularly for low production volumes. Our estimation shows that antivenom cost can vary from US$ 2.4 to US$ 25 per 10 mL vial, depending on the production volume, the plasma processing technology used and the titer achieved during the immunization stage. We conclude that interested laboratories and authorities of countries with population at risk should consider the possibility of a joint production to improve the process efficiency, lower the product unitary cost and obtain the necessary supply for their own demand or that of other countries in need.